Carbon dioxide reduction incentive for eco-industrial parks using bilevel fuzzy programming - Aguilar, Kyle Darryl T. (Animo Repository, 2017)
A potential approach in improving the sustainability of microalgae biofuels is through eco-industrial parks. Eco-industrial parks implement industrial symbiosis to generate economic and environmental benefits. The operation of an eco-industrial park involves the interaction of the park authority and the industry plants. Their conflicting objectives lead to the determination of a compromise solution between them. However, the industrial plants may not cooperate since the compromise solution is generally suboptimal for their respective objectives. The situation results to increased emissions of carbon dioxide which has the highest contribution to climate change among the greenhouse gases. Thus, a bi-level fuzzy optimization model for algae-based eco-industrial parks under carbon dioxide reduction incentives was proposed to address these. The results of the case study showed that the use of carbon dioxide reduction incentives improved both the environmental and economic aspects of the compromise solution obtained between the park authority and the industrial plants. The obtained cost savings per industrial plant were increased beyond their respective optimal values. It was noteworthy that the incentive used did not exceed its upper limit. Overall, the incentives enhanced the cost savings and carbon dioxide reduction of the algae-based eco-industrial park. In addition, the developed model can aid the decision-makers in designing algae-based eco-industrial parks and determining the appropriate regulatory frameworks to enhance the industrial symbiosis. Measures aside from carbon dioxide can also be used. © 2017 IEEE.